EKSISTENSI AJARAN SUFISME GURU TUA PADA MASYARAKAT KOTA PALU - Rusdin, Rusdin (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research revealed that the existence of the Old Master was not only a teacher who taught various scientific disciplines to his students but also a Sufi who was awarded Karamah from Allah SWT. Apart from that, the researcher also used Sayyed Hossein Naser's theory to analyze in depth the meaning of the substance contained in the Poetry of the Old Teachers related to the nature of God as the core of his Sufism teachings. In conclusion, the Old Master is a Sufi figure whose teachings originate from the teachings of the Prophet Muhammad and his companions. Then the implications of the Old Master's Sufism teachings have never been forgotten by his students since he was alive until now